Spectrum of gene mutations identified by targeted next‐generation sequencing in Chinese leukemia patients. Issue 9 (7th July 2020) - Yao, Hongxia; Wu, Congming; Chen, Yueqing; Guo, Li; Chen, Wenting; Pan, Yanping; Fu, Xiangjun; Wang, Guyun; Ding, Yipeng
Abstract: Background: Despite targeted sequencing have identified several mutations for leukemia, there is still a limit of mutation screening for Chinese leukemia. Here, we used targeted next‐generation sequencing for testing the mutation patterns of Chinese leukemia patients. Methods: We performed targeted sequencing of 504 tumor‐related genes in 109 leukemia samples to identify single‐nucleotide variants (SNVs) and insertions and deletions (INDELs). Pathogenic variants were assessed based on the American College of Medical Genetics and Genomics (ACMG) guidelines. The functional impact of pathogenic genes was explored through gene ontology (GO), pathway analysis, and protein–protein interaction network in silico. Results: We identified a total of 4, 655 SNVs and 614 INDELs in 419 genes, in which PDE4DIP, NOTCH2, FANCA, BCR, and ROS1 emerged as the highly mutated genes. Of note, we were the first to demonstrate an association of PDE4DIP mutation and leukemia. Based on ACMG guidelines, 39 pathogenic and likely pathogenic mutations in 27 genes were found. GO annotation showed that the biological process including gland development, leukocyte differentiation, respiratory system development, myeloid leukocyte differentiation, mesenchymal to epithelial transition, and so on were involved. Conclusion: Our study provided a map of gene mutations in Chinese patients with leukemia and gave insights into the molecular pathogenesis of leukemia. Abstract : We identified a total of 4, 655 single‐nucleotide variants and 614 insertions and deletions in 419 genes, in which PDE4DIP, NOTCH2, FANCA, BCR and ROS1 emerged as the highly mutated genes. Based on American College of Medical Genetics and Genomics guidelines, 39 pathogenic and likely pathogenic mutations in 27 genes were found. Our study provided a map of gene mutations in Chinese patients with leukemia and gave insights into the molecular pathogenesis of leukemia.